INVESTIGATIONS OF X-RAY ASYMMETRIC BBB-INTERFEROMETERS - Rostomyan, A. M. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2005)
Different versions of X-ray asymmetric interferometers with Bragg reflections are investigated. These interferometers with beam splitter, reflecting mirrors and analyzer are constructed from monolithic Si-crystal. Versions of BBB interferometers with optimal asymmetry are calculated and experimentally tested.